CONTRIBUTING FACTORS TO THE AUDIT DELAY (Jurnal Proaksi, 2022)
AbstractEven there are large amount of research investigating audit delay of company that are registered on the IDX has been finished, but there are still numerous results obtained. Therefore, the purpose of this paper is to analyze the factors that affect the audit delay, which consist of business size, public accounting firm size, audit committee, and audit complexity as independent variables while leverage as control variable. The data was taken from manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Based on the purposive sampling method, the number of samples obtained is 72 companies per year. The result of multiple linear regression shows that public accounting firm size has a negative effect on audit delay. Meanwhile, the business size, audit committee, and audit complexity did not show a significant effect on audit delayKeywords:  audit, audit delay, public accounting firm size